A Definitive Diagnosis of Primary Hodgkin Lymphoma on Endoscopic Biopsy Material Utilizing in-Depth Immunohistochemical Analysis. (2007) - Horne, Garnet; Medlicott, Shaun AC; Mansoor, Adnan; Lategan, Johan; Lai, Raymond; Beck, P
Abstract : The esophagus and stomach can be primary sites for Hodgkin lymphoma (HL). The pathognomonic feature of HL is the Reed-Sternberg cell. Because these cells can be rare in HL tumours, biopsies obtained via endoscopy are usually inadequate for establishing a definitive diagnosis. A case of a gastroesophageal junction primary HL is presented that was diagnosed on endoscopic biopsy material with the assistance of the immunohistochemical stains PAX5 and MUM1 which verified the presence of Reed-Sternberg cells. The patient was effectively treated for HL and avoided traditional laparotomy or thoracotomy procedures to obtain the diagnosis. This advanced immunohistochemical approach should be the standard in the diagnosis of primary gastrointestinal HL. An endoscopy-based approach should obviate more invasive, open biopsy procedures for establishing HL diagnosis.